The effects of solvent-exchange conditions on properties of sunflower pollen cryogels during fabrication - Soh, Megan Wenxi (Nanyang Technological University, 2024)
Pollen is a naturally occurring powdery substance produced by most types of flowers for the purposes of sexual reproduction. Given its abundance, it is relatively cheap to acquire pollen in large amounts. In terms of its uses, pollen is commonly recognized as a dietary supplement known for its health and medicinal benefits. Aside from this, the recent emergence of versatile biomaterials pollen-derived materials, such as pollen papers, pollen sponges, pollen cryogels, is paving the way forward in the application of biomaterial science, creating more use cases for pollen in areas such as drug delivery, medicine and therapeutics. However, the creation and optimization of said biomaterials remains an endeavouring feat as the space is constantly growing and evolving. Furthermore, there is much to learn when it comes to understanding how to analyse and optimise the traits of these cryogels, such as their water absorption properties, and their mechanical strength, structure, and stability. The abundance of opportunities found within this field suggests that the prospects of discovering new advanced manufacturing techniques and better applications remain high, making this field of research an increasingly attractive one.